Cloning of pullulanase gene from local isolated bacteria - Chee, Chit Lai (2005)
Pullulanases (pullulan-6-glucanohydrolase, EC 3.2.1.41) are debranching enzymes that are able to hydrolyze Î±-1,6-glycosidic linkages in pullulan and branched polysaccharides, producing maltotriose. Pullulanases are a member of family 13 glycosyl hydrolases or Î±-amylase family. Pullulanase are classified in two categories based on substrate specificity: Type I pullulanases that only hydrolyze Î±-1,6 linkages, and Type II pullulanases that hydrolyze Î±-1,6 and Î±-1,4 linkages. Due to this debranching ability, pullulanases are used in combination with Î±-glucosidase to improve saccharification rate and yield. In this project, local isolated bacteria were screened for the pullulanase activity by using AZCL-pullulan and Red pullulan. Bacteria S7 and bacteria P2 exhibited the ability to degrade AZCL-pullulan. However, Red pullulan plate growth with bacteria P2 exhibited halo zone. This result confirmed that bacteria P2, which was isolated from local resources, is a pullulanase-producer. I kb pullulanase gene fragment was amplified using PCR. Four conserved regions of amylolytic enzyme and a highly conserved region of pullulanase type I (YNWGYDP) were identified within the deduced amino acid sequence. Bacteria P2 was identified as Exiguohacterium,sp. MAA-I using 16S rRNA gene sequence analysis.